Pemanfaatan Limbah UPVC Sebagai Bahan Aditif pada CPHMA (Cold Paving Hot Mix Asbuton) - Ahnaf Saputra; Anwar Efendy; Nurul Hidayati; Adryan Fitrayudha; Adiman Fariyadin (Jurnal Talenta Sipil, 2026)
Advances in road technology have encouraged efforts to improve the quality of environmentally friendly and sustainable pavement materials. One potential local material is Asbuton (Buton Asphalt), which is used in Cold Paving Hot Mix Asbuton (CPHMA) products. However, the application of CPHMA is still limited due to its relatively low stability value. This study aims to analyze the effect of adding Unplasticized Polyvinyl Chloride (UPVC) waste on the characteristics of the CPHMA mixture and determine the optimum content that can improve its performance. The research method used was an experimental method with testing at the NTB Provincial DPU-PR Testing Center. The variation in UPVC waste addition was 0%, 1%, 2%, 3%, 4%, and 5% of the weight of asphalt, using the wet process mixing method. The tests included Marshall stability, flow, Void In Mixture (VIM), Void In Mineral Aggregate (VMA), and Void Filled with Bitumen (VFB) tests, referring to the 2018 Revised General Specifications for Highways. The results showed that adding 1% UPVC waste produced the highest stability value of 968 kg with flow and volumetric parameters that still met the standards. Adding more than 2% caused a decrease in stability due to increased air voids and decreased mixture homogeneity. Based on these results, the optimum level of UPVC waste in the CPHMA mixture was found to be 1%, which provided the best balance between the stability and durability of the mixture. This study indicates that the use of UPVC waste has the potential to improve the performance of CPHMA while supporting sustainable plastic waste management.